Забезпечення конкурентоспроможності фермерських господарств України: дис. ... доктора наук : 08.00.04 - Єременко, Денис Володимирович; Еременко, Денис Владимирович; Yeremenko, Denys (My University, 2019)
UK: Метою дисертаційної роботи є розроблення й обґрунтування теоретико-методологічних положень та науково-практичних рекомендацій щодо забезпечення конкурентоспроможності фермерських господарств. Предметом дослідження є сукупність теоретичних, методичних та практичних засад забезпечення розвитку конкурентоспроможності фермерських господарств. EN: The purpose of the dissertation is to develop theoretical and methodological principles, as well as to develop practical recommendations for ensuring the competitive functioning of farms. The subject of the study is a set of theoretical and methodological, methodological and practical principles for ensuring the competitive development of farms as an integral part of agrarian entrepreneurship.
Ensuring the competitiveness of Ukrainian farms
Keywords: фермерські господарства; конкурентоспроможність; виробництво; приватні господарства; сімейно-трудові господарства; farm; competitiveness; agrarian production; institute; agricultural co-operation